EFFECTS OF THE GLYCEMIA BEHAVIOR WITHIN PERSONS WITH TYPE 2 DIABETES MELLITUS (DM) ON A WALKING PROGRAM (Fiep Bulletin - online, 2015)
The objective of this research was to verify the effects of the glycemia behavior from persons with type 2 Diabetes Mellitus (DM) on a walking program, and they didn't make use of insulin and participated in the Diabetics Association of  Três de Maio, RS. The data was composed by 12 individuals (10 female and 2 male), with ages between 55 and 76 years. The dependent variables studied in this research were: capillary glycemia (GC), hemoglobin glucose (Hba) and Body Mass Index (BMI). GC was verified in 20 walking sessions (before and after); Hba was tested by laboratorial test in the beginning and at the end of the intervention; for BMI it was used OMS norms. The walking program happened during three months (36 sessions) and had a frequency of three times a week, with 30 minutes ( at the beginning of the program) to 50 minutes duration and between 40% to 65% of FC resting for intensity. The capillary glycemia and the hemoglobin glucose were analyzed by binomial distribution - Tests of Signs and Test of Wilcoxon. BMI was analyzed by Test "t" of Student for dependent samples. The level of significance was of 5%. The results demonstrated that, by the way the exercise program was made, such GC as Hba presented significant reductions statistically (p=0,05); although the program did not alter the BMI (p=0,87). Therefore, these results shows that the walking program proposed had a great importance to the glycemic control for individuals with type 2 diabetic, reducing Capillary Glycemia (GC) and the Hemoglobin Glucose (Hba). However, it was not able to change the Body Mass Index (IMC) of the diabetics.
Keywords: walking program; control glycemic; diabetes mellitus.